2018
DOI: 10.1186/s12939-018-0752-x
|View full text |Cite
|
Sign up to set email alerts
|

Equity of access to maternal health interventions in Brazil and Colombia: a retrospective study

Abstract: BackgroundReducing maternal mortality is a top priority in Latin American countries. Despite the progress in maternal mortality reduction, Brazil and Colombia still lag behind countries at similar levels of development.MethodsUsing data from the Demographic Health Survey, this study quantified and compared, by means of concentration indices, the socioeconomic-related inequity in access to four key maternal health interventions in Brazil and Colombia. Decomposition analysis of the concentration index was used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…As the CI is expressed in a number of ways algebraically in this study the most common in literature will be adapted for convenience; = 2 ( ; )………………………………… 1Equation 1denotes that the value of the concentration index is equal to the covariance between individual child health (ci) and child's relative rank (Ri), scaled by the mean of health in the population (μ) and then multiplied by 2 so as to ensure that the concentration index ranges between -1 and +1 [22][23][24].…”
Section: The Concentration Indexmentioning
confidence: 99%
“…As the CI is expressed in a number of ways algebraically in this study the most common in literature will be adapted for convenience; = 2 ( ; )………………………………… 1Equation 1denotes that the value of the concentration index is equal to the covariance between individual child health (ci) and child's relative rank (Ri), scaled by the mean of health in the population (μ) and then multiplied by 2 so as to ensure that the concentration index ranges between -1 and +1 [22][23][24].…”
Section: The Concentration Indexmentioning
confidence: 99%
“…A study in Bangladesh using DHS (Demographic and Health Survey) data in 2001 and 2010 presented an increasing percentage of antenatal care in urban (60% to 68%) and rural areas (37% to 49%). The research by Parmar and Banerjee 16 in Senegal and De La Torre et al 17 in Brazil and Colombia indicated that there was a gap in maternal health services utilization. A systematic review conducted by Çalışkan et al 18 confirmed that the earlier studies were dominated by the discussions of health services utilization; yet, they ignored the equity problems.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, within stratum the population is assumed to be affected similarly by the inequality. In order to quantify the degree of wealth-related inequality in outcome, concentration index (CI) has been extensively used [ 6 9 ]. This index quantifies the degree to which health services, for example are better targeted towards poorer or wealthier segment of the population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%